The RADEC Learning Model Improves Explanatory Text Writing Skill in Elementary Schools - Hidayat, Andi Reza; Firdaus, Fery Muhamad; Lusiana, Heni (Universitas Pendidikan Ganesha, 2023)
The skill of writing explanatory text is an essential skill to be mastered by elementary school students. However, most students still have low explanatory text writing skills. The purpose of this study was to analyze the Read, Answer, Discuss, Explain, and Create (RADEC) model in improving the writing skills of explanation texts of fifth grade elementary school students. This study used a quantitative approach with a Quasi Experimental Design type of Nonequivalent Control Group Design. The population in this study were fifth grade elementary school students consisting of two groups. The technique of determining the sample is purposive sampling. The data collection method in this study was a test using an explanatory text writing assessment rubric. Data analysis techniques in this study are descriptive statistical analysis and inferential statistical analysis. The results showed that there were significant differences in the skills of writing explanatory texts between the group that applied the RADEC model and the group that applied the conventional method. Thus, the RADEC model can improve the skills of writing explanatory texts of fifth grade elementary school students.